Respuesta :

To multiply these expression, multiply the numeric parts, and sum the exponents of the literal parts (because the variable is the same: we're using the power property [tex] a^b\cdot a^c = a^{b+c} [/tex]).

So, you have:

  • [tex] 3z^7 \cdot (4z^2) = 3\cdot 4 \cdot z^{7+2} = 12z^9 [/tex]
  • [tex] 6a^5 \cdot (6a^5) = 6\cdot 6 \cdot z^{5+5} = 36z^{10} [/tex]
  • [tex] 6b^4 \cdot (-3b^4) = 6\cdot (-3) \cdot b^{4+4} = -18b^8 [/tex]
  • [tex] 5x^4 \cdot (4x^2) = 5\cdot 4 \cdot x^{4+2} = 20x^6 [/tex]